Effective industry/institute interaction for developing entrepreneurial vision amongst engineers for the sustainable development of SMEs in India. (20th February 2004) - Wani, V.P.; Garg, T.K.; Sharma, S.K.
The development of entrepreneurship amongst engineers will be an effective mechanism of luminous renaissance in technology innovations, helpful in the removal of regional imbalance and sustainable growth of SMEs. An engineer, through self-employment as a career, can bring about a technical revolution that can meet the challenges of the emerging scenarios of globalisation and liberalisation, with a key element of competition rather than protection. This paper discusses the strategies for developing entrepreneurial vision amongst engineers, the necessity of the engineer as entrepreneur, the significance of industry/institute interaction, the role of engineering education and the impact of engineering education in the growth of small and medium enterprises. As per the survey carried out, the authors find the relevance of the entrepreneurial concept and capability amongst engineers when selecting career options.